KEBIJAKAN UPAH DAN INDUSTRIALISASI - Prijono Tjipto herijanto (UGM, 1999)
The last two decades has seen a shift in employed in the agricultural sector fell from 55,91 percent to 16,15 percent, while over the same periode the figure for the industrial sector rose from 8.4 percent to 13,3 percent.